Divide and conquer - Ryan, Carrie (New York : Scholastic, 2012)
When thousands of Viking warriors descend on medieval Paris, Dak is captured and forced to work with the invaders while Sera and Riq defend the city, a situation that places them on opposing sides.
Sequel to: A mutiny in time.
Suggested level: primary, intermediate.
105649
Keywords: Time travel -- Juvenile fiction; Vikings -- Juvenile fiction; Best friends -- Fiction; Imaginary wars and battles -- Fiction; Adventure and adventurers -- Fiction; Science fiction; Fiction. -- Vikings; Fiction. -- Time travel; Paris (France) -- History -- Juvenile fiction; France -- Paris; Paris (France) -- History -- Juvenile fiction; Science fiction; Time travel; Fiction; History; Juvenile works; Adventure fiction; Fantasy fiction